Development of efficient integrated management package against sweet potato weevil (Cylas formicarius [Fabricius, 1798]) - Mohammad Monirul Hasan TIPU; Raunak JAHAN; Jubaidur RAHMAN; Md Mizanur RAHMAN; Md Ariful ISLAM; Md Mosiur Rahman Bhuyin APU (Acta Agriculturae Slovenica, 2021)
The sweet potato weevil (Cylas formicarius, 1798) is one of the most damaging sweet potato pests. To prevent an economic crop loss, it is very important to develop a suitable and efficient integrated pest management strategy. A field experiment was set up with three replications at Jamalpur to select the best integrated management package from eight different treatments against sweet potato weevil. The results showed that the lowest percentage of infestation by number (2.94 %) and mass (3.22 %) was found when the crop was planted on November 01; earthing-up for two times, Carbofuran 5G was sprayed @ 15 kg ha-1 at 60 days after planting with irrigation and tuber was harvested at 130 days after planting. The marketable yield (23.75 kg) and percent increase of yield than control (50.86 %) performed the highest in the same combination. These findings suggested an effective integration of different management strategies to reduce sweet potato weevil infestation in Bangladesh successfully.